Oxygen Reduction Activity and Stability of Composite Pdx/Co-Nanofilms/C Electrocatalysts in Acid and Alkaline Media - An, LuLu; Chen, Yumei; Shi, Jianchao; Cao, Jianliang; Liu, Baozhong; Yang, Juan (Frontiers in Chemistry, 2018)
The morphology tuning of Pd and Pd-M nanoparticles is one of the significant strategies to control the catalytic activity towards oxygen reduction reaction (ORR). In this study, composite Pdx/Co-nanofilms/C electrocatalysts of Pd nanoparticles implanted onto Co nanofilms were synthesized on an immiscible ionic liquid (IL)/water interface for ORR. The Pd nanoparticles implanted onto Co nanofilms show a marked distortion of crystal lattice and surface roughness. These Pdx/Co-nanofilms/C electrocatalysts exhibit enhanced activity for ORR compared with Pd/C and PdxCo/C catalysts in both acid and alkaline solutions, in which the Pd3/Co-nanofilms/C catalyst displays the highest ORR mass activity. The superior ORR mass activities of the fabricated Pdx/Co-nanofilms/C catalysts may be mainly attributed to their larger catalytic areas, which are conferred by the rough surface of Pd nanoparticles with a distorted crystal lattice, and the synergistic effect between the surface Pd atoms and the 2D Co nanofilm substrate. The relationship between ORR mass activity and Pd/Co atom ratio varies in different electrolytes. Furthermore, by using proper heat-treatment methods, the Pdx/Co-nanofilms/C catalysts exhibit improved cycling stability compared with pure Pd/C catalyst after extended potential cycling.